Reading the works of Verism through the magazines and critics of XIXth century. Text editions, lexical maps and thematic dictionaries in a user-oriented portal - Bruno, Denise; Canzoneri, Giuseppe; Cristofaro, Salvatore; Di Silvestro, Antonio; Mazzagufo, Laura; Spampinato, Daria (Umanistica Digitale, 2025)
The COVerLeSS project (Corpus Online del Verismo tra Letteratura, Storia e Società) explores Italian Verismo within the field of Periodical Studies, drawing on ongoing digitization and preservation initiatives in libraries and cultural institutions across Italy and Europe. The project aims to develop an integrated, open-access web platform that brings together journals, reviews, and essays on Verismo’s literary production. This platform integrates Digital Humanities tools and technologies for textual analysis, combining a digital edition with XML/TEI structural and descriptive markup, managed through TEI Publisher, quantitative lexical analysis, and the development of ontologies based on specific encoding elements. The focus is on the creation of a hybrid edition-archive, or knowledge site, where textual reading is complemented by both synchronic and diachronic data analysis. A central feature is the development of a lexical map, the Verbum dictionary, that links secondary literature on Verismo to primary sources through an interactive timeline (Ver-in-time). Designed to be user-friendly and inclusive, the platform accommodates different levels of expertise, from students to researchers, offering flexible ways to navigate, explore, and engage with diverse texts. By highlighting lexical patterns and key concepts, the project reveals the deep cohesion within this literary movement, providing a fresh perspective on a pivotal period in Italian cultural and literary history: the post-unification era.